ANALYSIS OF THE EFFECTIVENESS OF CONCESSIONAL LENDING IN AGRO-INDUSTRIAL COMPLEX OF RUSSIA - Inna Rykova (Вестник Северо-Кавказского федерального университета, 2022)
The article considers approaches to evaluating the effectiveness of concessional lending, which was introduced in 2017 as a new mechanism to promote the development of agriculture, and ensuring access of agricultural producers and small farms to low-cost funding sources.